2020
DOI: 10.3389/fmicb.2020.574626
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evolutionary Patterns of Burkholderia cenocepacia and B. multivorans During Chronic Co-infection of a Cystic Fibrosis Patient Lung

Abstract: During chronic respiratory infections of cystic fibrosis (CF) patients, bacteria adaptively evolve in response to the nutritional and immune environment as well as influence other infecting microbes. The present study was designed to gain insights into the genetic mechanisms underlying adaptation and diversification by the two most prevalent pathogenic species of the Burkholderia cepacia complex (Bcc), B. cenocepacia and B. multivorans. Herein, we study the evolution of both of these species during coinfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 116 publications
0
6
1
Order By: Relevance
“…Among the eight isolates of patient 1, no gradual increase in antimicrobial resistance was observed, as the isolates collected in 2011 were already fully resistant to virtually all compounds tested (Fig 2). We found an average mutation rate of 15 SNPs/year (S4 Fig) which was much higher than earlier reported values for B. multivorans (2.2-2.4 SNPs/year), B. cenocepacia (1.7-2.1 SNPs/year) or B. dolosa (2.1 SNPs/year) [39,40,42,43].…”
Section: Plos Pathogenscontrasting
confidence: 76%
See 1 more Smart Citation
“…Among the eight isolates of patient 1, no gradual increase in antimicrobial resistance was observed, as the isolates collected in 2011 were already fully resistant to virtually all compounds tested (Fig 2). We found an average mutation rate of 15 SNPs/year (S4 Fig) which was much higher than earlier reported values for B. multivorans (2.2-2.4 SNPs/year), B. cenocepacia (1.7-2.1 SNPs/year) or B. dolosa (2.1 SNPs/year) [39,40,42,43].…”
Section: Plos Pathogenscontrasting
confidence: 76%
“…Comparative genomic analyses of Bcc isolates sampled from single patients in the course of chronic infections have shown that diversifying lineages can co-exist in the CF lungs for many years, with limited rates of evolution (as proxied by single nucleotide polymorphisms), i.e. around 2.1 to 2.4 SNPs/year [38][39][40][41][42][43]. This evolution within the lungs of CF patients can result In concentric circles, from the center and outward are depicted: 1) the GC skew, 2) the GC content, 3) the genomic islands detected by the software IslandViewer 4 (in purple), the prophages detected with Phaster (green) and the secondary metabolites identified by antiSMASH (in blue), 4) a total of five SNP densities, we separated the isolates from 2011 and the isolate from 2018 in patient 2 as we regard them as two separate acquisition events, 5) and 6) the annotated features found on the negative and positive strand respectively.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Moreover, Bcc bacteria have also been associated with nosocomial infections in immunocompromised and immunocompetent patients hospitalized for reasons unrelated to CF and CGD [ 21 ]. Currently, B. cenocepacia and B. multivorans are the Bcc species most frequently isolated from patients in Europe and North America [ 22 ]. B. cenocepacia is multidrug resistant and transmissible among CF patients, and causes a fatal condition known as “cepacia syndrome” which is characterized by necrotizing pneumonia and progressive respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Bcc strains are intrinsically resistant to most antibiotics (Rhodes and Schweizer 2016), turning those infections difficult to eradicate. Burkholderia cenocepacia and Burkholderia multivorans are the most predominant Bcc species infecting CF patients worldwide (Hassan et al 2020). B. cenocepacia possess a large genome (approximately 8 Mb), composed by multiple replicons, the chromosome 1 (3.9 Mb), chromosome 2 (3.2 Mb), megaplasmid pC3 (0.88 Mb), and plasmid pBCJ2315 (92 kb) (Holden et al 2009).…”
Section: Introductionmentioning
confidence: 99%